2012
DOI: 10.1111/j.1751-1097.2012.01132.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Basic Amino Acids on Photoreaction of Ketoprofen in Phosphate Buffer Solution

Abstract: Photoreaction of ketoprofen (KP), one of the widely used nonsteroidal anti-inflammatory drugs (NSAIDs), was studied with transient absorption spectroscopy in phosphate buffer solution (pH 7.4) in the presence of basic amino acids of histidine (His), lysine (Lys) and arginine (Arg). Deprotonated form of KP (KP(-)) excited with UV-light irradiation gave rise to carbanion through a decarboxylation reaction. It was found that carbanion abstracted a proton from the side chain of the protonated amino acids to yield … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…In the phosphate buffer solution of pH 7.4, almost all KP exists in the deprotonated form of KP (KP − ) because of its acidity (p K a = 4.7). According to the previous report , an intense band around 600 nm appearing immediately after the laser irradiation was due to KP carbanion, and the band around 525 nm at 1.7 μs after the laser was assigned to EBPH. The same spectra were obtained with Tyr.…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations
“…In the phosphate buffer solution of pH 7.4, almost all KP exists in the deprotonated form of KP (KP − ) because of its acidity (p K a = 4.7). According to the previous report , an intense band around 600 nm appearing immediately after the laser irradiation was due to KP carbanion, and the band around 525 nm at 1.7 μs after the laser was assigned to EBPH. The same spectra were obtained with Tyr.…”
Section: Resultsmentioning
confidence: 83%
“… *Reference ; †For amino acids and dipeptides, correction of the concentration should be required because actual quencher for carbanion was the protonated form to the side chain of basic amino acids and dipeptides ; ‡Reference ; §Reference ; ∥Reference ; ¶This work. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the website of IHSS, amino acids are important compositions of DOM (IHSS website). Suzuki et al have demonstrated that the basic amino acids, including histidine, lysine and arginine, can accelerate the photoreaction of ketoprofen (Suzuki et al, 2012). Here, we used glycine and histidine to test the effect of amino acid on PABA photolysis (Fig.…”
Section: Part 3 Verification Of the Possible Mechanismsmentioning
confidence: 94%